2016
DOI: 10.4049/jimmunol.1501870
|View full text |Cite
|
Sign up to set email alerts
|

IRF4 and IRF8 Act in CD11c+ Cells To Regulate Terminal Differentiation of Lung Tissue Dendritic Cells

Abstract: Dendritic cells (DCs) initiate immune responses in barrier tissues including lung and skin. Conventional DC subsets, CD11b− (cDC1s) or CD11b+ (cDC2s), arise via distinct networks of transcription factors involving IRF4 and IRF8 and are specialized for unique functional responses. Using mice in which a conditional Irf4 or Irf8 allele is deleted in CD11c+ cells, we determined if IRF4 or IRF8 deficiency beginning in CD11c+ cDC precursors (pre-cDCs) changed the homeostasis of mature DCs or pre-DCs in the lung, der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
80
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 49 publications
(82 reference statements)
9
80
1
1
Order By: Relevance
“…Analysis of Irf4 fl/fl .Cd11cCre mice revealed that cardiac cDC2 (CD172α + CD24 +/− ) were only slightly reduced (Figures 2C and 2E). However, a significant reduction in CD24 + cDC2s was observed, suggesting that IRF4 is important for their terminal differentiation, as described in the lung (Bajaña et al., 2016). Because IRF4 has also been implicated in regulating cDC2 migration (Bajaña et al., 2012), we next studied cDC2 frequency in the heart-draining mediastinal lymph node (mLN) (Figures 2D and 2E).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Analysis of Irf4 fl/fl .Cd11cCre mice revealed that cardiac cDC2 (CD172α + CD24 +/− ) were only slightly reduced (Figures 2C and 2E). However, a significant reduction in CD24 + cDC2s was observed, suggesting that IRF4 is important for their terminal differentiation, as described in the lung (Bajaña et al., 2016). Because IRF4 has also been implicated in regulating cDC2 migration (Bajaña et al., 2012), we next studied cDC2 frequency in the heart-draining mediastinal lymph node (mLN) (Figures 2D and 2E).…”
Section: Resultsmentioning
confidence: 55%
“…As described in other tissues, cDC2s and moDCs expressed CD11b, whereas cDC1s expressed CD103. cDC1s uniformly expressed CD24, whereas cDC2s were separated into CD24 + and CD24 − cDC2s, as described for lung cDC2s (Bajaña et al., 2016). Expression of CADM1, a universal cDC1 marker (Guilliams et al., 2016, Gurka et al., 2015), was restricted to cDC1s.…”
Section: Resultsmentioning
confidence: 99%
“…The monocyte and macrophage marker CD64 (Tamoutounour et al, 2012) was highly expressed on CD14 + cells, and expressed at much lower levels on cDC2 and cDC1 (Figure S1A–C), further confirming our subset delineation strategy. In fluorescence images, CD13 + Clec9A + and CD1c + cells displayed a dendritic cell morphology and expressed the canonical cDC1 and cDC2 transcription factors IRF8 and IRF4 (Aliberti et al, 2003; Bajana et al, 2016), respectively (Figure 1F). Our results thus establish human tissue CD13 hi CD141 hi Clec9A + cells as cDC1, and CD1c + Sirp-α + cells as cDC2.…”
Section: Resultsmentioning
confidence: 99%
“…The transcription factor BATF3 is required for development of CD103 + cDCs, and these cells are therefore absent in Batf3 −/− mice 39 . A different transcription factor, IRF4, is required for the development of CD11b + cDCs, and mice bearing a floxed allele of Irf4 ( Irf4 fl/fl ) as well as a Cre recombinase gene under control of a Cd11c promoter ( Cd11c-Cre Irf4 fl/fl mice) have markedly reduced numbers of CD11b + cDCs 40 . Surprisingly, after Th17 adoptive transfer and OVA/HDE challenges, Batf3 −/− mice, Cd11c-Cre Irf4 fl/fl mice, and WT mice all had similar levels of airway inflammation, Tomato + Th17 cell numbers and IL-17 cytokine levels (Figure 7A–D).…”
Section: Resultsmentioning
confidence: 99%